Critical Barriers to Implementing Risk Assessment and Management Practices (RAMP) in the Iranian Construction Sector - Chileshe, Nicholas; Hossein, M. Reza; Jepson, Jacqueline (Penerbit Universiti Sains Malaysia, 2016)
Late completions, frequent work stoppages and cost overruns are common issues in developing countries. Effective risk management (RM) can be utilised to address these common construction issues; however, the uptake of risk management within the Iranian construction industry, as in many developing nations, is limited. This study explored why RM is not used through a questionnaire survey of 90 professionals in the Iranian construction industry. The findings show that professionals in the industry perceive the three greatest barriers to be (1) a lack of experience among practitioners, (2) the lack of available risk management consultants and (3) a lack of knowledge and necessary skills. In contrast, the professionals believed that the least common barriers were tight scheduling of projects and costs associated with risk management implementation. No significant differences were found between the perceptions of the three sub-groups—contractors, consultants and clients (private and public)—regarding the barriers to risk management. The study contributes to the field by providing insights into what causes the low level of implementation of risk assessment and management practices (RAMP) in Iran. It is anticipated that this type of study will result in raising the level of awareness about practices designed to improve risk management in developing countries. The study advocates a number of solutions for addressing the identified barriers. These solutions can be implemented or used as guidelines by construction companies and policy makers in other developing countries confronting similar problems.